FAKTOR-FAKTOR PENUNJANG KEMAMPUAN BELAJAR DI SEKOLAH DASAR NEGERI LAE LANGGE KECAMATAN SULTAN DAULAT KOTA SUBULUSSALAM - Mawardi, Mawardi; Indayani, Sri (Jurnal Pendidikan Islam, 2019)
This research aims to find out the right method as a solution for students whose abilities are limited in learning, knowing the obstacles that are obstacles for students both internal and external. This research was conducted in 2 (two) cycles, cycle I to obtain general data that would be used as a sample in the implementation, cycle II which was the researcher's success point. This research was carried out for eight weeks. Based on the results obtained in the second cycle has shown significant results with excellent categories. In this study used several relevant methods using a collaborative approach that is students are encouraged to be able to accept others, face challenges, and work in teams. After being tested on several elementary schools in Subulussalam City, the collaborative system is very effective in finding solutions to students' difficulties in learning. So, the product in the form of a collaborative approach can be used for subsequent research with the hope that it can function as a step in solving problems in learning in elementary schools.